2016
DOI: 10.1016/j.surg.2015.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Resection of primary tumor site is associated with prolonged survival in metastatic nonfunctioning pancreatic neuroendocrine tumors

Abstract: Background Non-functioning pancreatic neuroendocrine tumors (NFpNET) present with distant metastases in up to 50% of patients. It is unknown whether removal of the primary tumor in patients with NFpNET and metastases is beneficial. Methods We used the Surveillance, Epidemiology and End Results (SEER) database to identify patients with NFpNET and distant metastases. The primary outcome measure in this study was overall survival. Results We identified 882 patients with metastatic NFpNET and survival data. 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 17 publications
(33 reference statements)
1
71
0
2
Order By: Relevance
“…Localization of the primary tumor is highly relevant in the management of this patient population because complete resection of the primary tumor and metastases is the treatment goal for patients with well-differentiated NET metastases (2). Even if the metastases are not completely resectable, debulking surgery can improve symptom control in patients with endocrine symptoms and may improve survival (2)(3)(4).…”
mentioning
confidence: 99%
“…Localization of the primary tumor is highly relevant in the management of this patient population because complete resection of the primary tumor and metastases is the treatment goal for patients with well-differentiated NET metastases (2). Even if the metastases are not completely resectable, debulking surgery can improve symptom control in patients with endocrine symptoms and may improve survival (2)(3)(4).…”
mentioning
confidence: 99%
“…Nevertheless survival is higher in specialized centers and may depend on the multidisciplinary approach [10]. Another group showed that the resection of the primary tumor improves patient outcome in non-functional pNET [22]. Despite advanced tumor stages we found relatively long disease free survivals of 21 months in group Ia and 8.7 months in group IIa.…”
mentioning
confidence: 66%
“…Cytoreduction may be considered if removal of over 90% of the tumour mass is possible, even if hepatic metastases are present [164] (*evidence level 3). Removal of 90% of the visible tumour mass is possible in only 5-15% of cases [165].…”
Section: Advanced F-pnetsmentioning
confidence: 99%
“…Cytoreductive procedures are acceptable [167,168] (*evidence level 2). Resective treatment of hepatic metastases of PNETs is considered only in NETs of G1 and G2 [164] (*evidence level 3). It depends on the resectability of the lymph nodes, lack of micronodular or non-resectable dissemination in the peritoneum, or distant metastases outside the abdominal cavity [169].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%